Triple inhaled therapy in COPD patients: determinants of prescription in primary care. (July 2019) - Vetrano, Davide L.; Zucchelli, Alberto; Bianchini, Elisa; Cricelli, Claudio; Piraino, Alessio; Zibellini, Marco; Ricci, Alberto; Onder, Graziano; Lapi, Francesco
Abstract: Objective: To assess the incidence and determinants of the triple inhaled therapy in chronic obstructive pulmonary disease (COPD) primary care patients. Methods: Data derived from the Health Search Database (HSD) gathering information on 700 Italian general practitioners. A cohort of COPD patients, prescribed for the first time with inhaled treatments, was followed-up between January 2002 and December 2014. The outcome was the first incident prescription of a triple inhaled therapy, namely the combination of inhaled corticosteroids (ICS), long-acting beta agonists (LABA), and long-acting muscarinic antagonists (LAMA). Cox regressions were used to test the association (hazard ratios, HR) between candidate determinants and the outcome. Results: Out of 17589 patients (mean age 71.1 ± 11.3 years; 37.4% females), 3693 (21%) were prescribed with a triple inhaled therapy during follow-up. Older age (HR = 1.79 to 2.61), current and former smoking habit (HR = 1.72 and 1.66), higher GOLD stage (HR = 1.45 to 2.79), the number of moderate and severe COPD exacerbations (HR = 1.10 to 2.63), and heart failure (HR = 1.17) resulted statistically significantly associated with an increased incident prescription of the triple inhaled therapy. Female sex (HR = 0.80) and some comorbidities (HR = 0.21 to 0.87) resulted negatively associated with the outcome. Furthermore, patients initially treated with LAMA (HR = 1.5) and LABA/ICS (HR = 1.23) were more likely to escalate to the triple therapy, than those on LABA. Conversely, patients initially treated with ICS presented a negative hazard (HR = 0.72). Conclusions: The knowledge of demographic and clinical determinants of the escalation to the triple inhaled therapy in real-world COPD patients may help clinicians to better personalize respiratory pharmacological treatments of their patients, and inform international societies that issue clinical guidelines. Highlights: One fifth of primary care patients with COPD are prescribed with triple inhaled therapy over 4.5 years. Older age, cigarette smoking, COPD severity and heart failure trigger the escalation to the triple inhaled therapy. The knowledge of such factors may help GPs and specialist to better personalize pharmacological treatment in COPD patients.